2009
DOI: 10.1161/circresaha.108.189837
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NAD(P)H:Quinone Oxidoreductase 1 Prevents Arterial Restenosis by Suppressing Vascular Smooth Muscle Cell Proliferation

Abstract: Abstract-Abnormal proliferation and migration of vascular smooth muscle cells (VSMCs) are important pathogenic mechanisms in atherosclerosis and restenosis after vascular injury. In this study, we investigated the effects of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
60
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 34 publications
2
60
0
Order By: Relevance
“…In support of this model is the finding that NQO1 Ϫ/Ϫ mice have a reduced ratio of NAD ϩ /NADH (36). Furthermore, it was lately shown that an increase in the NAD ϩ /NADH ratio induced by NQO1 results in AMPK activation (77), which subsequently sets the stage for further activation of PGC-1-by the AMPK-Sirt1 axis (21). Overall, our findings provide evidence for an additional layer of complexity in the regulation of PGC-1␣ expression and activity, which is mediated by NQO1 and the process of degradation by default (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…In support of this model is the finding that NQO1 Ϫ/Ϫ mice have a reduced ratio of NAD ϩ /NADH (36). Furthermore, it was lately shown that an increase in the NAD ϩ /NADH ratio induced by NQO1 results in AMPK activation (77), which subsequently sets the stage for further activation of PGC-1-by the AMPK-Sirt1 axis (21). Overall, our findings provide evidence for an additional layer of complexity in the regulation of PGC-1␣ expression and activity, which is mediated by NQO1 and the process of degradation by default (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Longer-term studies may also accentuate the contribution of very slow-eluting NP medicines. Beyond paclitaxel, the variety of antiproliferative treatments can be expanded to sirolimus and its analogs, newer developed drugs (40), and combination treatments.…”
Section: Discussionmentioning
confidence: 99%
“…6) Several phytochemicals inhibiting oxidative stress have a beneficial effect in atherosclerosis and restenosis via their direct antioxidant actions. [7][8][9] Therefore, NQO-1 induction is likely to be of key importance in protecting against oxidative stress and suppressing atherosclerosis development. 7) Rho guanosine 5′-triphosphatases (GTPases) participate in cell adhesion, vesicle trafficking, cell cycle progression, gene expression and differentiation.…”
mentioning
confidence: 99%
“…[7][8][9] Therefore, NQO-1 induction is likely to be of key importance in protecting against oxidative stress and suppressing atherosclerosis development. 7) Rho guanosine 5′-triphosphatases (GTPases) participate in cell adhesion, vesicle trafficking, cell cycle progression, gene expression and differentiation. 10,11) Members of the Rho small GTPase and Rho kinase play a role in cardiovascular physiology 12,13) .…”
mentioning
confidence: 99%